CONTENT PLAN OF NOMINACENTRIC PROVERBS IN DIFFERENT SYSTEMS LANGUAGES (based on the materials of Russian, Uzbek and Kazakh languages) (Scientific journal of the Fergana State University, 2023)
This article analyzes in detail the subject-thematic groups of proverbial funds of the Russian, Uzbek and Kazakh languages, examines the characteristic features and content properties of nominative paremias of the three compared languages. The meaning and meaning of some proverbs in languages   of different systems are interpreted, it is proved that the proverbs of the peoples of the world are identical in semantic terms, since the ethnoi of the planet are members of one large family called humanity.  The place and meaning of proverbs are indicated, which in the language cover all spheres of life of human society, it is proved that they are an invaluable wealth of oral folk art and a reliable means of educating a spiritually perfect young generation, it is confirmed that it is impossible to name any area of   material and spiritual activities of society, which would not be reflected in proverbs.